Proteus syndrome and immunodeficiency. Issue 3 (1st March 2000) - Hodge, D; Misbah, S A; Mueller, R F; Glass, E J; Chetcuti, P A J
Abstract : A 10 year old boy with Proteus syndrome presented with a pericardial effusion of unknown aetiology. Immunological investigation revealed low serum IgG and IgA, accompanied by low levels of specific antibodies to pneumococcal and haemophilus type B polysaccharides. Circulating lymphocyte surface marker profile revealed T and B cell lymphopenia. This is the first report of hypogammaglobulinaemia occurring in the Proteus syndrome.